Influence of alkali metals on water dynamics inside imidazolium-based ionic liquid nano-domains - Dziubinska-Kühn, Katarzyna; Maddah, Mina; Pupier, Marion; Matysik, Jörg; Viger-Gravel, Jasmine; Kowalska, Magdalena; Karg, Beatrice (Frontiers in Chemistry, 2022)
The global need to expand the design of energy-storage devices led to the investigation of alkali metal - Ionic Liquid (IL) mixtures as a possible class of electrolytes. In this study, 1D and 2D Nuclear Magnetic Resonance (NMR) and Electrochemical Impedance Spectroscopy (EIS) as well as Molecular Dynamics (MD) simulations were used to study the intermolecular interactions in imidazolium-based IL - water - alkali halide ternary mixtures. The 1H and 23Na 1D and 1H DOSY NMR spectra revealed that the presence of small quantities of NaCl does not influence the aggregation of water molecules in the IL nano-domains. The order of adding ionic compounds to water, as well as the certain water and NaCl molecular ratios, lead to the formation of isolated water clusters. Two ternary solutions representing different orders of compounds mixing (H2O+ IL + NaCl or H2O+ NaCl + IL) showed a strong dependence of the initial solvation shell of Na+ and the self-clustering of water. Furthermore, the behaviour of water was found to be independent from the conditions applied during the solution preparation, such as temperature and/or duration of stirring and aging. These findings could be confirmed by large differences in the amount of ionic species, observed in the ternary solutions and depending on the order of mixing/solute preparation.